Bridging Formal and Conceptual Semantics Selected papers of BRIDGE-14 - Balogh, Kata; Petersen, Wiebke (Studies in Language and Cognition, 2017)
The articles in this volume are the outcome of the successful BRIDGE Workshop held in Düsseldorf in 2014. The workshop gathered a number of distinguished researchers from formal semantics and conceptual semantics and aimed to initiate a deeper conversation and collaboration instead of separating the two sides as competing views. The workshop provided a platform to further discuss parallelisms on specific semantic issues on the one hand and on the other hand to confront opposed claims from the two different perspectives. This volume represents a selected number of high-quality papers presented at the workshop featuring various approaches to meaning from linguistics, logic and philosophy of language.